Mediação de conflitos e o julgamento moral de ações: qual o tipo de parcerias em escolas? - Guedes, Júlio Cledson de Oliveira (2013)
Conflict is a natural phenomenon within society. The seeking for peaceful solutions to such conflicts is the natural basis of the legal system of any society that seeks to cultivate certain social values. As society cultivates values that favor the coexistence of collective conflicts that arise are to be seen as a threat to those values of social life. So there is natural interest that these conflicts are resolved in a more orderly as possible to maintain the social and moral values that promote this coexistence. The phenomenon of violence within the school has been growing in recent years, worrying school managers from large urban centers seeking outlets and ways to deal with this social phenomenon. Thus comes the mediation of conflicts school is a technique brought the judiciary into the schools with the intention of bringing new air school and with the promise of mitigating the phenomenon of violence within the school and will bring that good relationships inside school. Conflict Mediation has as principle agreements and dialogues between teachers and students and among students who quarrel within the school environment. In the formation of this team of mediators within the school are chosen students who are considered by the managers of the school as students who cause disturbances to the environment of the classroom. These students are brought to team of mediators to promote conflict resolution within the school. One of the strategies to achieve breakthrough contain the growing phenomenon of school violence. This study was interested in understanding how the technique of conflict mediation school affects the development of moral judgment of the students involved in the mediation of conflicts within the school and Kohlbergian/Piagetian perspective. Methodology was used in the Piagetian clinical method using interviews with dilemmas. Two groups of students were used in the study: a group of students and mediators in another group of students did not mediate the same school that served as a research field. Making a comparison of the responses given by each group of students so we can analyze from the perspective of Piaget and Kohlberg. The survey data show a strong heteronomy still present in the two groups of students surveyed. And thus providing a reflection on the techniques of mediation of school conflicts and their role in building a Piagetian autonomy and a Kohlberg´s "fair community".